2003
DOI: 10.1053/jlts.2003.50189
|View full text |Cite
|
Sign up to set email alerts
|

Executive summary from the Intraoperative Advisory Council on Donation After Cardiac Death of the United Network for Organ Sharing: Practice guidelines

Abstract: The number of organs recovered from asystolic donors is less than anticipated and is explained partially by negative attitudes held by health care providers. To understand the reasons for these beliefs and find solutions, the United Network for Organ Sharing under contract with the Department of Health and Human Services convened the Intraoperative Advisory Council on Donation After Cardiac Death in September, 2001. The Council found that, unlike other medical specialties, operating room health care providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Several white papers and guidelines regarding DCD organ recovery have been published in the past decade, and this literature has established basic, generalized practices which are currently employed throughout the United States 19‐22 . These guidelines have firmly established several ethical principles including the importance of separating the role of the care team from the role of the recovery team, as well as surgical principles such as descriptions of the super‐rapid recovery technique and the importance of minimizing fDWIT and CIT 12‐14,23,24 . However, little guidance has been published regarding the peri‐procedural details that go beyond these important, but general principles.…”
Section: Discussionmentioning
confidence: 99%
“…Several white papers and guidelines regarding DCD organ recovery have been published in the past decade, and this literature has established basic, generalized practices which are currently employed throughout the United States 19‐22 . These guidelines have firmly established several ethical principles including the importance of separating the role of the care team from the role of the recovery team, as well as surgical principles such as descriptions of the super‐rapid recovery technique and the importance of minimizing fDWIT and CIT 12‐14,23,24 . However, little guidance has been published regarding the peri‐procedural details that go beyond these important, but general principles.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reasons have been cited for poor utilization of DCD organs and include; suboptimal organ function/survival, lack of DCD protocols at institutions or within organ procurement organizations (OPOs), higher manpower effort/expense, unwillingness of the medical community to accept and uncertainty of perioperative staff with end of life care (20,21). In our early efforts at establishing a DCD protocol, operating room extubation was considered mandatory for all extrarenal organ recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, the United Network for Organ Sharing Intraoperative Council on DCD recommended that critical procedures, such as the withdrawal of intensive care administration of medications or the declaration of death, should not fall upon anesthesiologists as a delegated act [23]. They pointed out that patients and their families should receive the same continuum of care as if they were still admitted to the intensive care unit.…”
Section: Irreversible Cessation Of Cardiopulmonary Functionmentioning
confidence: 99%
“…Findings from the United Network for Organ Sharing Intraoperative Council on DCD revealed that allied operating room personnel viewed anesthesiologists as the 'captain of the ship', depending upon them for leadership and advice [23]. They thought that anesthesiologists' views influenced the attitudes of operating room personnel towards DCD.…”
Section: Irreversible Cessation Of Cardiopulmonary Functionmentioning
confidence: 99%